Supporting the Evolution of BPMN Models through e-VOL BPMN - Campos, Ursula; Lopes, Adriana; Conte, Tayana (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2020)
During software maintenance, software models play a fundamental role, as they assist in understanding the software that will be corrected or evolved. Business process models, generally produced using Business Process Modeling and Notation (BPMN), help understanding the business processes supported by software. Therefore, these models are instrumental in maintaining corporate software. However, it is common that during software maintenance, models related to the software are not updated. Thus, the models are inconsistent with the version in use of the software, becoming increasingly obsolete over time. Given that, we developed the e-VOL BPMN technique to support BPMN models' evolution during software maintenance. The objective of e-VOL BPMN is to assist software engineers and developers, with little experience in BPMN notation, to carry out the necessary evolutions in the processes supported by the software. We evaluated the e-VOL BPMN in two experiments, and the results showed evidence that e-VOL BPMN helps the evolution of BPMN models in an appropriate manner. With this technique, such professionals can keep BPMN models up to date. This makes it easier to understand the processes supported by the software, which reduces the time and cost of future maintenance. Furthermore, understanding these processes correctly can reduce undue modifications to the software, contributing to the quality of the maintained software.